Afritoxinones A and B, dihydrofuropyran-2-ones produced by Diplodia africana the causal agent of branch dieback on Juniperus phoenicea - Evidente, Antonio; Masi, Marco; Linaldeddu, Benedetto T.; Franceschini, Antonio; Scanu, Bruno; Cimmino, Alessio; Andolfi, Anna; Motta, Andrea; Maddau, Lucia (PHYTOCHEMISTRY, 2012)
Two phytotoxic dihydrofuropyran-2-ones, named afritoxinones A and B. were isolated from liquid culture of Diplodia africana. a fungal pathogen responsible for branch dieback of Phoenicean juniper in Italy. Additionally, six others known metabolites were isolated and characterized: oxysporone, sphaeropsidin A, epi-sphaeropsidone, R-(-)-mellein, (3R,4R)-4-hydroxymellein and (3R,4S)-4-hydroxymellein. The structures of afritoxinones A and B were established by spectroscopic and optical methods and determined to be as (3aS{*},6R{*}-,7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-o ne and (3aR{*},6R{*},7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-on e, respectively. The phytotoxic activity of afritoxinones A and B and oxysporone was evaluated on host (Phoenicean juniper) and non-host plant (holm oak, cork oak and tomato) by cutting and leaf puncture assay. Oxysporone proved to be the most phytotoxic compound. This study represents the first report of secondary metabolites produced by D. africana. In addition, the taxonomic implications of secondary metabolites in Botryosphaeriaceae family studies are discussed. (C) 2012 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Afritoxinones A and B; Botryosphaeriaceae; Diplodia africana; Juniperus phoenicea; Phytotoxins

Screening of 18 Mediterranean plant species for volatile organic compound emissions - Owen, S; Boissard, C; Street, R A; Duckham, S C; Csiky, O; Hewitt, C N (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.
Keywords: Arbutus unedo; Biogenic emissions; branch enclosure; Chrysanthemum praecox; cistus incanus; Cistus salvifolius; Cytisus sp.; Dittrichia sp.; Erica arborea; Erica multiflora; Helichrysum stoechas; isoprene; Juniperus oxycedrus; Juniperus phoenicea; Monoterpene; myrtus communis; Phillyrea angustifolia; Pinus pinea; Quercus cerris; Quercus ilex; Rubus fruticosus; Spartium junceum; VOCs